To the Question about the Reasons for the Attack of the Crimean Khan Mengli Giray against Kiev (1482) and the Breach of the Peace with Polish King Casimir IV Jagiellon (according to the Genoese documents) » - V.P. Gulevich (Золотоордынское обозрение)
Contemporary researchers consider it as a proven fact that Grand Prince of Moscow Ivan III instigated the attack of the Crimean khan Mengli Giray against Kiev in 1482. Italian documents of 1480s allow us to provide an alternative explanation for these events. After the Ottoman conquest of Caffa in 1475 the Genoeses planned to recover their colony. For this purpose they sent their emissaries to Mengli Giray who were to both examine the situation in Crimea and incite the khan for an uprising in Caffa against Turkish rule. To secure the success of their plan they also planned to persuade the Polish king Casimir Jagiellon to participate in the uprising. Polish ruler approved a plan in words, but did not provide any practical support. This, in turn, prompted Mengli Giray to attack on Kiev. Purpose of the study: to find out the reasons for the Tatar attack against Kiev in 1482. Objective: to establish the circumstances that led to the attack on Kiev in 1482 and the rupture of peaceful relations between Mengli Giray and Casimir IV. Novelty of the study: based on the little-known sources the author for the first time provides an alternative explanation for the rupture of peaceful relations between Mengli Giray and Casimir IV.